2019
DOI: 10.1534/genetics.119.302391
|View full text |Cite
|
Sign up to set email alerts
|

Tel1/ATM Signaling to the Checkpoint Contributes to Replicative Senescence in the Absence of Telomerase

Abstract: Telomeres progressively shorten at every round of DNA replication in the absence of telomerase. When they become critically short, telomeres trigger replicative senescence by activating a DNA damage response that is governed by the Mec1/ATR and Tel1/ATM protein kinases. While Mec1/ATR is known to block cell division when extended single-stranded DNA (ssDNA) accumulates at eroded telomeres, the molecular mechanism by which Tel1/ATM promotes senescence is still unclear. By characterizing a Tel1-hy184 mutant vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Since the kinase activity of Tel1 is essential only for some of the Tel1 functions, 23 , 25 , 27 , 45 , 52 , 53 , 54 , 55 , 56 but tel1Δ exo1Δ and tel1-kd exo1Δ cells show the same hypersensitivities to CPT, MMS, and HU ( Figure 1 A), we investigated how Exo1 supports the viability of tel1-kd cells. Furthermore, we focused on CPT treatment, because the lack of Exo1 and Tel1 activity strongly enhance the hypersensitivity to this agent.…”
Section: Resultsmentioning
confidence: 99%
“…Since the kinase activity of Tel1 is essential only for some of the Tel1 functions, 23 , 25 , 27 , 45 , 52 , 53 , 54 , 55 , 56 but tel1Δ exo1Δ and tel1-kd exo1Δ cells show the same hypersensitivities to CPT, MMS, and HU ( Figure 1 A), we investigated how Exo1 supports the viability of tel1-kd cells. Furthermore, we focused on CPT treatment, because the lack of Exo1 and Tel1 activity strongly enhance the hypersensitivity to this agent.…”
Section: Resultsmentioning
confidence: 99%
“…As Tel1 promotes ssDNA generation at both DSBs and telomeres [ 141 ], the delayed senescence in Tel1-deficient telomerase-negative cells can be due to a reduced amount of telomeric ssDNA. By studying the senescence phenotype of telomerase-deficient cells lacking Tel1 or expressing the hyperactive Tel1-hy184 mutant variant, which has been identified because of its ability to compensate for the lack of Mec1 function [ 142 ], it was shown that Tel1-hy184 anticipates senescence, while the lack of Tel1 or of its kinase activity delays it [ 143 ]. Neither Tel1-hy184 nor Tel1 kinase defective variant affects the generation of ssDNA at telomeres, suggesting that Tel1 function in promoting senescence is not directly linked to ssDNA generation.…”
Section: Consequences Of Telomere Shorteningmentioning
confidence: 99%
“…In S. cerevisiae , Mec1-Ddc2 (orthologues of human ATR-ATRIP) and Tel1 (orthologue of human ATM) are two sensor kinases to perceive DSBs [ 70 ]. Mec1-Ddc2 senses ssDNA through interaction with RPA [ 71 ], while Tel1 is recruited to DSBs and activated by the MRX complex [ 72 ]. It was found that the mec1 tel1 null mutant showed a great increase (~13000 fold) in chromosomal rearrangement, of which most are chromosome translocations [ 73 , 74 ].…”
Section: Spontaneous and Genotoxic Factor-induced Chromosomal Rearmentioning
confidence: 99%